Kinetic study of carbon monoxide methanation over mesoporous Ni-Mo catalyst prepared by a hydrothermal method. (February 2019) - Jiaying, Zhang
The kinetics of carbon monoxide methanation over Ni-Mo-SiO2 catalyst were studied. The model was developed based on catalyst tests carried out in a fixed-bed reactor at a reaction temperature varied from 300 °C to 450 °C under a pressure from 0.1 to 1.5 MPa with a weight hourly space velocity of 60, 000 mL h −1 g −1 . An orthogonal design method was adopted to select test points with temperature, pressure, and feed compositions as factors. Based on the experimental observations, a Langmuir–Hinshelwood equation kinetic model was formulated and its parameters were estimated by fitting the experimental data implemented in MATLAB. The activation energy for the formation of CH4 was 45.4 kJ mol −1 and comparing the experimental and model-predicted data showed that the proposed model gives a reasonable fit with an average absolute relative deviation of ±9.8%.